Experimental study on specific grinding energy and particle size distribution of maize grain, stover and cob - Fu, Jun; Xue, Zhao; Chen, Zhi; Ren, Luquan (International Journal of Agricultural and Biological Engineering, 2020)
Reducing the particle size of biomass is of great significance for rational and efficient utilization of biomass. In this study, maize grain, stover, and cob were comminuted at different speeds (2000-2800 r/min) by hammer mill with a mesh size of 2.8 mm. The mechanical energy for smashing three selected samples was obtained directly through the sensor and data testing system. Experimental results demonstrated that the maize cob had the highest total specific energy while the maize grain had the lowest (135.83-181.10 kW·h/t and 27.08-36.23 kW·h/t, respectively). In addition, for the same material, higher hammer mill speed generated more specific energy consumption. And the effective specific energy of maize stover had a similar trend to the total specific one. However, the effective specific grinding energy of maize cob and grain increased initially and then decreased with the increase of rotating speed. The fitting curves of the specific energy to mill speeds were determined, and the range of determination coefficients of the regression equation was 0.933-0.996. Particle size distribution curves were drawn by sieving the pulverized particles of the three samples based on a series of standard sieves. Fourteen relevant parameters characterizing the particle size distribution were calculated according to the screening data. Calculation results demonstrated that larger rotational speed leads to smaller particle sizes. Combining the size parameters, distribution parameters, and shape parameters, it was found that the distributions of the three samples all exhibit a distribution of “well-graded fine-skewed mesokurtic”. The Rosin-Rammler function was considered to be suitable for characterizing the particle size distribution of maize grain, stover, and cob particles with a coefficient of determination between 0.930 and 0.992.Keywords: maize grain, maize stover, maize cob, specific energy, particle size distribution, comminutionDOI: 10.25165/j.ijabe.20201304.5327Citation: Xue Z, Fu J, Chen Z, Ren L Q. Experimental study on specific grinding energy and particle size distribution of maize grain, stover and cob. Int J Agric & Biol Eng, 2020; 13(4): 135–142.